The Historical Formation And Development Of Pedagogical Terminology In Karakalpak And English Languages - Sultanova Dilfuza Kamalovna (International Journal Of Literature And Languages, 2025)
This article examines the historical formation and development of pedagogical terminology in Karakalpak and English, emphasizing the linguistic, cultural, and social factors that shaped their evolution. Although the two languages belong to distinct linguistic families, both have developed rich terminological systems that reflect their educational philosophies, national identities, and scientific influences. The study highlights how Karakalpak pedagogical terminology emerged from traditional cultural values, oral literature, and later Soviet and global scientific influence, whereas English terminology evolved through extensive borrowing from Latin, Greek, and French, as well as the contributions of major modern educational theorists. The analysis also compares pedagogically oriented proverbs in both languages, demonstrating how cultural values are transmitted through language. Ultimately, the article argues that despite structural and historical differences, both Karakalpak and English pedagogical terminologies reveal universal tendencies driven by globalization, technological development, and modern educational reforms.